Democracy at work in Malaysia - Mohd. Azizuddin Mohd. Sani; Ummu Atiyah Ahmad Zakuan (Penerbit Universiti Utara Malaysia, 2017)
The prediction is that the 14th General Election (14thGE) is coming earlier than when it should be, as early as March 2017, instead of May 2018. On the one hand, with the DAP-led opposition in disarray for the last 18 months, since the departure of PAS, and on the other, the UMNO-led BN becoming more resolved and combative, the events leading to the forthcoming election promises more fireworks. The complexity of facts, fictions, perceptions and perspectives in making sense of the forthcoming 14thGE are intricate.